Ultrahypofractionated versus hypofractionated and conventionally fractionated radiation therapy for localized prostate cancer: A systematic review and meta-analysis of phase III randomized trials. (July 2020) - Lehrer, Eric J.; Kishan, Amar U.; Yu, James B.; Trifiletti, Daniel M.; Showalter, Timothy N.; Ellis, Rodney; Zaorsky, Nicholas G.
Highlights: UHRT is becoming a widely adopted treatment in localized prostate cancer. UHRT offers similar rates of disease-free survival to CFRT and HFRT at 85%. Grade 2+ late GI toxicity is approximately 12% across all modalities. Grade 2+ late GU toxicity is approximately 20% across all modalities. Abstract: Introduction: To characterize the efficacy (5-year disease-free survival [DFS]) and safety (incidence of grade 2+ late gastrointestinal or genitourinary toxicity) of ultrahypofractionated radiation therapy (UHRT) versus hypofractionated radiation therapy (HFRT) and conventionally fractionated radiation therapy (CFRT) by comparing patients treated on phase III protocols. Methods: A PICOS/PRISMA/MOOSE protocol was used to identify eligible studies. Weighted random effects meta-analyses were conducted using the DerSimonian and Laird method. Wald-type tests were used to compare treatment modalities for each outcome, where the null hypothesis was rejected for p < 0.05. Results: Seven studies were included that consisted of 6795 patients (2849 CFRT, 3357 HFRT, and 589 UHRT). Median age was 68 years. Summary effect sizes for 5-year DFS were 85.1% (95% CI: 82.1%–87.8%) for CFRT, 86% (95% CI: 83%–88.7%) for HFRT, and 85% (95% CI: 80%–87%) for UHRT ( p = 0.66 and p = 0.8 for CFRT vs. HFRT and CFRT versus UHRT, respectively). Summary effect sizes for late grade 2+ gastrointestinal toxicity were 12.1% (95% CI: 9.2%–15.4%) for CFRT, 14.6% (95% CI: 9.9%–20%) for HFRT, and 10% (95% CI: 7%–13%) for UHRT ( p = 0.41 and p = 0.09 for CFRT versus HFRT and CFRT versusus UHRT, respectively). Summary effect sizes for late grade 2+ genitourinary toxicity were 19.4% (95% CI: 10.7–29.9%) for CFRT, 20.4% (95% CI: 10.2%–32.9%) for HFRT, and 18% (95% CI: 15%–22%) for UHRT ( p = 0.89 and p = 0.92 for CFRT versus HFRT and CFRT versus UHRT, respectively). Conclusion: Ultrahypofrationated regimens appear to offer similar levels of safety and efficacy to CFRT and HFRT. These findings are hypothesis-generating and require further validation by ongoing prospective trials.